2021
DOI: 10.3389/fonc.2021.736448
|View full text |Cite
|
Sign up to set email alerts
|

Chemoradiotherapy Is Superior to Radiotherapy Alone in Esophageal Cancer Patients Older Than 65 Years: A Propensity Score-Matched Analysis of the SEER Database

Abstract: IntroductionRadiotherapy (RT) is the main treatment for unoperated esophageal cancer (EC) patients. It is controversial whether adding chemotherapy (CT) to RT is beneficial for elderly EC patients. The purpose of our study was to compare the efficacy of chemoradiotherapy (CRT) with RT alone for non-surgical elderly esophageal cancer patients.MethodsA total of 7,101 eligible EC patients older than 65 years diagnosed between 2000 and 2018 were collected from the Surveillance, Epidemiology, and End Results (SEER)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…For example, in a large retrospective analysis of the SEER database, 3020 elderly patients (≥ 65 years) with esophageal cancers treated with chemoradiation or radiotherapy alone were analyzed. In this analysis, the five-year overall and cancer-specific survival rates were only 13% and 20%, respectively; comparing the treatment modalities by propensity-score matching, a significant survival benefit of chemoradiotherapy versus radiotherapy was evident regardless of patient age (8). Other retrospective studies of elderly patients with esophageal cancer reported 5-year OS rates in the range of 5 -36% after (chemo)radiotherapy (17,18).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…For example, in a large retrospective analysis of the SEER database, 3020 elderly patients (≥ 65 years) with esophageal cancers treated with chemoradiation or radiotherapy alone were analyzed. In this analysis, the five-year overall and cancer-specific survival rates were only 13% and 20%, respectively; comparing the treatment modalities by propensity-score matching, a significant survival benefit of chemoradiotherapy versus radiotherapy was evident regardless of patient age (8). Other retrospective studies of elderly patients with esophageal cancer reported 5-year OS rates in the range of 5 -36% after (chemo)radiotherapy (17,18).…”
Section: Discussionmentioning
confidence: 66%
“…However, despite the high clinical importance, available data for esophageal cancer therapy in the elderly are mainly derived from retrospective studies except for one recent prospective randomized study that reported survival of elderly esophageal cancer patients after chemoradiotherapy with S-1 or radiotherapy alone (8,9,(13)(14)(15)(16)(17). Most reports analyzed elderly esophageal cancer patients with both adenocarcinomas and SCCs, and most of these studies have demonstrated a survival benefit for additional concomitant chemotherapy, including the only published prospective study to date with an exclusively elderly patient population (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29,31,32 Moreover, a recent study demonstrated that chemoradiotherapy was superior to radiotherapy alone in elderly EC patients. 33 Hence, there is no doubt that active therapy could prolong the survival of patients. However, in clinical settings, chemotherapy and radiotherapy are usually administered to patients with good performance status (PS); hence, selection bias could exist in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In five subgroups based on the age stratification (65-69; 70-74; 75-79; 80-84; ≥ 85 years), the 3- and 5-year OS showed significant benefits in the chemoradiotherapy group compared with the RT alone group (all P < 0.05). The authors thus concluded that chemoradiotherapy could significantly improve survivals in non-surgical EC patients older than 65 years[ 8 ]. Although the modes [3-dimensional conformal RT (3DCRT) or IMRT], dosage (50-60 Gy), range (prophylactic irradiation of high-risk lymphatic drainage areas or not), and concurrent chemotherapy regimens (including platinum plus 5-fluorouracil, platinum plus paclitaxel, platinum plus capecitabine, and single-agent regimen) of RT varied among different studies[ 9 - 13 ], the safety and efficacy of concurrent chemoradiotherapy in elderly patients have been well demonstrated, with the ORR 56.7%-84.0%, the median OS 9-35 mo, and the 2-year OS rate 27%-78%.…”
Section: Discussionmentioning
confidence: 99%